3D printing structure loaded carbon material composite catalyst as well as preparation method and application thereof
The catalyst for load-modified carbon material is prepared by 3D printing technology, combined with hydrogen peroxide and/or persulfate for oxidation treatment, which solves the problem of removing organic pollutants in antibiotic-contaminated water, and achieves efficient, stable and environmentally friendly water treatment effects.
Patent Information
- Application Number
- CN202411399986.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art is difficult to efficiently remove organic pollutants in antibiotic-contaminated water, especially antibiotics are not easy to degrade and conventional sewage treatment technologies cannot be completely removed. In addition, traditional catalyst activation methods have problems such as metal sludge formation or external energy supply.
3D printing technology is used to prepare a composite catalyst of load-modified carbon material. Modified carbon material is prepared by vibrating ball mill and loaded on a 3D printing support to form a catalyst with uniform layered arrangement structure and ordered pore size distribution, combining hydrogen peroxide and/ Or persulfate is oxidized.
It has achieved efficient removal of organic pollutants, especially antibiotics, and has good stability and recycling performance, avoiding the formation of metal sludge and external energy consumption, and is suitable for industrial applications.
Smart Images

Figure CN119281314A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a 3D printed structure-loaded carbon material composite catalyst and a preparation method and application thereof, belonging to the technical field of catalysts. Background Art
[0002] Since the successful clinical application of penicillin in 1944, antibiotics have been widely developed and increasingly used as the most important drugs to improve human health, treat bacterial infections and promote the growth of animal husbandry. However, studies have found that only 10% of antibiotics are metabolized in humans and animals, and the rest are excreted through urine and feces and released into the water environment. The harm of antibiotics entering the environment to human and environmental health has attracted widespread attention. However, antibiotics are not easy to degrade and conventional sewage treatment technology often cannot completely remove them from water bodies. Therefore, there is an urgent need for an efficient and environmentally friendly water pollution treatment technology to treat antibiotic wastewater.
[0003] Advanced oxidation processes (AOPs) can effectively oxidize and even mineralize refractory organic pollutants. Among them, peroxymonosulfate advanced oxidation (PMS-AOP) has been shown to be a more effective wastewater treatment technology. Compared with hydroxyl-based AOPs, the OO bond of PMS breaks to produce sulfate radicals (SO4· - ), which has stronger oxidation ability and longer survival time in water environment. However, PMS is stable and it is difficult to decompose into SO4· - Therefore, it is necessary to further activate PMS to generate active free radicals for the oxidative degradation of organic pollutants.
[0004] The activation of PMS in the PMS-AOP process is achieved by using various catalyst materials such as metal ions / oxides, chemical, thermal, photo and ultrasonic processes. Although transition metal ions / oxides can effectively activate PMS, it can lead to secondary pollution such as the formation of metal sludge or metal leaching into the water environment. In other AOPs, thermal, photo and ultrasonic treatment processes require external energy to activate PMS. In recent years, metal-free carbonaceous materials have been widely used to activate PS / PMS materials to effectively degrade organic pollutants in water environments. Among them, activated carbon has the advantages of large specific surface area, porous structure, rich oxygen-containing functional groups, huge specific surface area and high porosity, and the activation of persulfate does not require external energy, which effectively avoids metal leaching and is widely used in the activation of persulfate.
[0005] Fixed bed reactors (FBRs) can be used for multiphase processes such as separation, distillation, and catalytic reactions. The fillers in the reactor can increase the contact area between the two phases, thereby improving the process efficiency. For example, the synergistic effect of catalysts with various oxidants (such as ozone, hydrogen peroxide, and persulfate) or alternative energy sources (such as photons, electricity, or heat) is beneficial for the degradation of difficult-to-treat wastewaters. In this type of reactor, the fillers are usually arranged in randomly packed spherical or cylindrical materials. However, when FBRs are used for industrial applications, they may face problems such as significant pressure loss, uneven void distribution, and reduced mass transfer efficiency. Therefore, regulating the preparation and operating conditions of the catalyst in the FBR is crucial to improve its wastewater treatment capacity.
[0006] 3D printing technology, also known as additive manufacturing technology, is a rapid prototyping technology that uses a computer to build a digital model and control the printer to print powder particles layer by layer to construct devices. At present, there are four main printing methods, namely stereolithography (SLA), fused deposition modeling (FDM), selective laser sintering (SLS), and digital light processing (DLP). The basic principle of DLP 3D printing technology is that digital light sources are projected layer by layer on the surface of liquid photosensitive resin in the form of surface light, and then solidified layer by layer. Compared with traditional 3D printing technology, this technology has developed rapidly due to its high molding precision and low price, and has received widespread attention.
[0007] Among them, 3D printing doping printing technology provides new possibilities for various application fields by precisely controlling the addition of materials during the printing process. However, there are still some technical challenges in doping technology. For example, the density of each component in the photosensitive resin is different during doping printing, and stratification will occur after standing for a long time. The stratified resin cannot be cured under the same exposure parameters; the photosensitive resin exhibits the characteristic of absorbing water when exposed to the environment. Excessive environmental humidity will increase the proportion of moisture in the local microenvironment of the resin and reduce the effective ingredients; changes in ambient temperature will lead to inconsistent reaction efficiencies of each cured layer, unbalanced stress inside the material, and ultimately lead to severe deformation of the molded parts. These factors will lead to stability problems during doping printing. To avoid stability problems during doping printing, supported catalysts are a good choice. 3D printing supported catalysts are catalysts prepared by 3D printing technology, in which the supported structure refers to the active substance being fixed on the carrier material to form a catalyst with a specific structure and function. Compared with traditional catalysts, 3D printing supported catalysts have the advantages of low cost, high precision, and controllable structure, especially in the preparation of complex structure catalysts. It shows great potential. Summary of the invention
[0008] Purpose of the invention: The first purpose of the present invention is to provide a 3D printed structure-loaded carbon material composite catalyst with a modified carbon material as a matrix having a uniform layered arrangement structure and uniform pore size distribution. A composite catalyst loaded with modified carbon material is obtained by controlling the carbon material and 3D printed model prepared under different ball milling frequencies. The second purpose of the present invention is to provide a method for preparing the 3D printed structure-loaded carbon material composite catalyst, and the third purpose of the present invention is to provide the application of the 3D printed structure-loaded carbon material composite catalyst in the activated hydrogen peroxide and / or persulfate oxidation treatment of organic wastewater.
[0009] Technical solution: The present invention discloses a 3D printed structure-loaded carbon material composite catalyst, wherein the catalyst is prepared by loading a modified carbon material on a 3D printed carrier, wherein the modified carbon material is obtained by vibrating and ball milling the carbon material.
[0010] Furthermore, the carbon material is one or more of graphene, carbon nanotubes, activated carbon, and biochar.
[0011] Furthermore, the material of the 3D printing carrier is one or more of vinyl resin, polyurethane resin, epoxy resin, and photosensitive curing resin.
[0012] Furthermore, the structure of the 3D printing carrier is a three-dimensional ordered variable porous structure, a structure containing parallel straight channels, an ordered mesh structure or a honeycomb structure.
[0013] Furthermore, the average particle size of the loaded modified carbon material is 0.1-2 mm.
[0014] Furthermore, the modified carbon material loading mass is 0.50-5.00 g / 1-50 m 2 g -1 Specific surface area of 3D printing carrier.
[0015] Furthermore, the frequency of the vibration ball mill is 10-100 Hz.
[0016] The method for preparing the 3D printed structure-supported carbon material composite catalyst of the present invention comprises the following steps:
[0017] (1) Preparation of modified carbon material: treating carbon material by vibration ball milling to obtain modified carbon material;
[0018] (2) Preparation of 3D printing carrier: pour the 3D printing carrier into the slot of the DLP 3D printer, load the STL file of the required 3D structure into the slicing software, print, clean and dry according to the set model printing parameters to obtain the 3D printing carrier;
[0019] (3) Loading the modified carbon material on a 3D printed carrier: placing the 3D printed carrier into the modified carbon material, and oscillating the modified carbon material to load the 3D printed carrier, thereby obtaining a 3D printed structure-loaded carbon material composite catalyst.
[0020] Furthermore, in step (2), the model printing parameters are layer thickness 0.05 mm, exposure time 2.0 s, light off time 0.5 s, bottom exposure time 45.0 s, Z-axis lifting distance 6.00 mm, and the number of bottom layers is 6.
[0021] Furthermore, in step (3), the frequency of oscillation is below 50 Hz.
[0022] The present invention also includes the use of the 3D printed structure-loaded carbon material composite catalyst in the treatment of organic wastewater by activated hydrogen peroxide and / or persulfate oxidation.
[0023] Furthermore, the organic wastewater contains antibiotics, and the antibiotic is ofloxacin.
[0024] Furthermore, the reaction conditions for using the 3D printed structure-loaded carbon material composite catalyst of the present invention to activate hydrogen peroxide and / or persulfate oxidation to treat organic wastewater are: normal pressure, the reaction atmosphere is one of air, oxygen, and nitrogen, and the reaction temperature is 10 to 80°C.
[0025] Furthermore, the dosage of hydrogen peroxide and / or potassium persulfate is 1 to 20 times the content of the antibiotic.
[0026] Furthermore, the dosage of the 3D printed structure-loaded carbon material composite catalyst of the present invention is 1 to 20 times the content of the antibiotic.
[0027] Furthermore, the persulfate is ammonium persulfate, potassium persulfate or sodium persulfate.
[0028] Furthermore, the concentration of hydrogen peroxide is 30% or less.
[0029] The present invention obtains a modified carbon material by vibrating and grinding the carbon material, and loads the modified carbon material on a 3D printed model to obtain the composite catalyst. In the presence of hydrogen peroxide and / or persulfate, the catalytic efficiency is improved by controlling the reaction atmosphere, reaction temperature, catalyst structure, catalyst dosage and organic wastewater flow rate. The highly efficient activated hydrogen peroxide / persulfate 3D printed composite catalyst can effectively and quickly remove organic pollutants in water bodies, and is a catalyst with excellent performance suitable for Fenton / persulfate oxidation systems.
[0030] The catalyst carrier prepared by the DLP 3D printing technology of the present invention has a relatively flat surface and a structure with uniform layered arrangement. The pore size distribution is uniform, and the structure has interconnected ordered pores inside. The pore channel presents a relatively regular stepped structure, which overcomes the limitation of pore distribution, promotes the dispersion of carbon materials on the bracket, and reflects the advantages of 3D printed catalysts in the internal structure. DLP printing technology helps to alleviate mass transfer limitations by combining the filling structure with a carefully designed fluid channel. The composite catalyst adopts a layered structure, and the designed catalytic sites help to accelerate chemical reactions and improve process efficiency. The application of the 3D printed structure-loaded carbon material composite catalyst in activating peroxymonosulfate (PMS) to degrade ofloxacin has good application potential in wastewater treatment.
[0031] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0032] (1) The vibration ball milling method of the present invention is simple and the technology is mature. The vibration ball milling modification effectively increases its roughness and specific surface area, which is conducive to providing more active components;
[0033] (2) The surface of the 3D printed model of the present invention is relatively flat, and the three-dimensional ordered variable porous structure carrier is arranged in a uniform layered structure. The pore size distribution is uniform, and the regular step-like structure formed between the pores promotes the dispersion of the modified carbon material in the structural channel, thereby providing more active sites;
[0034] (3) The 3D structure-supported carbon material composite catalyst prepared by the present invention has a simple process and good stability. By controlling the geometric shape of the carrier, the porosity distribution is optimized and the channel effect is minimized to effectively improve the overall catalytic activity;
[0035] (4) The 3D structure-loaded carbon material composite catalyst prepared by the present invention has good recovery performance and a long service life, exhibits excellent stability, and meets the requirements of potential industrial applications.
[0036] (5) The present invention relates to a composite catalyst used in a Fenton / persulfate oxidation system, which can quickly and efficiently remove antibiotics from wastewater. The catalyst exhibits advantages such as high catalytic activity, good stability, structural controllability, and easy recycling in a Fenton / persulfate system, and is suitable for use in the field of sewage treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is the SEM image of activated carbon modified by vibration ball milling;
[0038] Figure 2This is a SEM image of the 3D printing carrier prepared in Example 2 before and after loading modified activated carbon;
[0039] Figure 3 Model diagram of preparing a 3D printing carrier for comparative example 3;
[0040] Figure 4 The bar graph is a removal rate bar graph of ofloxacin by the composite catalyst prepared in Examples 1-3;
[0041] Figure 5 The figure is a bar graph showing the removal rate of ofloxacin by the composite catalyst prepared in Example 2 and Comparative Example 3;
[0042] Figure 6 This is a graph showing the stability test results of the composite catalyst prepared in Example 2. DETAILED DESCRIPTION
[0043] Embodiment 1:
[0044] (1) Preparation of modified activated carbon:
[0045] The activated carbon was vibrated and ball-milled at a frequency of 10 Hz for 15 min using a multi-sample tissue grinder (Tiss-24 from Shanghai Jingxin Industrial Development Co., Ltd.), and sieved using a standard test sieve to obtain modified activated carbon with an average pore size of 1.45 mm.
[0046] The activated carbon modified by vibration ball milling was analyzed by scanning electron microscope. Figure 1 Show. Figure 1 The scanning electron microscope images of activated carbon before and after vibration ball milling modification, where (a) is a 1μm magnified image, (b) is a 5μm magnified image, and (c) is a 10μm magnified image. Figure 1 It can be seen that the surface of the modified activated carbon is rough and the pore structure is densely distributed.
[0047] (2) Preparation of 3D printing carrier
[0048] 2g of photosensitive curing resin (purchased from Shenzhen Zongwei Cube Technology Co., Ltd.) was poured into the resin tank of the DLP 3D printer (Photon Mono version of Shenzhen Zongwei Cube Technology Co., Ltd.), and the STL file of the three-dimensional ordered variable porous structure (obtained from https: / / www.thingiverse.com / ) was loaded into the slicing software, and printed according to the set model parameters (layer thickness 0.05mm, exposure time 2.0s, light off time 0.5s, bottom exposure time 45.0s, Z-axis lifting distance 6.00mm, and 6 bottom layers). After printing, the uncured resin on the outer surface of the 3D printed model was cleaned with ethanol and pure water, and dried to constant weight to obtain a 3D printed carrier with a three-dimensional ordered variable porous structure. The specific surface area of the obtained 3D printed carrier with a three-dimensional ordered variable porous structure was tested, and the measured surface area was 44m 2 g -1 .
[0049] (3) Modified activated carbon loaded on 3D printing carrier:
[0050] The 3D printing carrier of the three-dimensional ordered variable porous structure is placed in a beaker containing the modified activated carbon prepared in step (1), the vortex mixer vibration frequency is adjusted to 50Hz, and the beaker is vibrated steadily to ensure that the modified activated carbon is fully in contact with the carrier, and the modified activated carbon is loaded on the carrier through the electrostatic interaction between the modified activated carbon and the resin. After 10 minutes of vibration, the 3D printing carrier is taken out, and the 3D printing carrier is washed with deionized water to remove the modified activated carbon that is not firmly attached. The 3D printing carrier loaded with modified activated carbon is dried to finally obtain a composite catalyst of a three-dimensional ordered variable porous structure loaded with modified activated carbon. By weighing and calculating, it can be seen that the loading amount of the modified activated carbon is 0.50±0.05g (loading amount=yx, wherein x is the mass of the 3D printing carrier before loading activated carbon, and y is the mass of the 3D printing carrier loaded with activated carbon).
[0051] Embodiment 2:
[0052] The catalyst preparation process is the same as in Example 1:
[0053] (1) Preparation of modified activated carbon:
[0054] The activated carbon was vibrated and ball-milled at a frequency of 40 Hz for 15 min to obtain modified activated carbon with an average pore size of 0.21 mm;
[0055] (2) Preparation of 3D printing carrier:
[0056] Pour 2g of photosensitive curing resin into the resin tank of the DLP 3D printer, and load the STL file of the three-dimensional ordered variable porous structure into the slicing software. Print according to the set model parameters (layer thickness 0.05mm, exposure time 2.0s, light off time 0.5s, bottom exposure time 45.0s, Z-axis lifting distance 6.00mm, bottom layer number 6 layers). After printing, clean the uncured resin on the outer surface of the 3D printed model with ethanol and pure water, dry to constant weight, and obtain a 3D printed carrier with a three-dimensional ordered variable porous structure. The surface area of the obtained 3D printed carrier with a three-dimensional ordered variable porous structure was measured to be 44m 2 g -1 .
[0057] (3) Modified activated carbon loaded on 3D printing carrier:
[0058] The 3D printed carrier with three-dimensional ordered variable porous structure was placed in a beaker containing modified activated carbon material, the vortex mixer vibration frequency was adjusted to 50Hz, and the beaker was vibrated steadily to ensure that the modified activated carbon was fully in contact with the carrier. The modified activated carbon was loaded on the carrier through the electrostatic interaction between the modified activated carbon and the resin. After vibrating for 10 minutes, the 3D printed carrier was taken out, and the 3D printed carrier was washed with deionized water to remove the activated carbon that was not firmly attached. The 3D printed carrier loaded with modified activated carbon was dried to finally obtain a composite catalyst with three-dimensional ordered variable porous structure loaded with modified activated carbon. The responsible mass of the modified activated carbon was 0.75±0.05g obtained by weight measurement yx.
[0059] The 3D printed carrier and the 3D printed structure-loaded carbon material composite catalyst prepared in this example were analyzed by scanning electron microscopy. Figure 2 shown. Figure 2 The SEM images of the 3D printed carrier loaded with modified activated carbon prepared in Example 2 before and after comparison, where (a) is a three-dimensional ordered variable porous structure carrier image, (b) is a composite catalyst model image loaded with modified activated carbon. (c) is a SEM image of the 3D printed structure loaded with carbon material composite catalyst. Figure 2 It can be seen that the appearance of the 3D printed carrier is white. From the inside of the 3D printed carrier, the internal lines are evenly staggered, and there is space between the upper and lower layers of the printed lines, which reflects the advantages of the 3D printed catalyst in the internal structure. After loading the modified activated carbon, the entire composite catalyst has a black appearance. Figure 2 In (c), it can be clearly seen that the modified activated carbon is evenly dispersed on the 3D printing carrier. It can be found that the regular stepped structure formed between the pores of the 3D printing carrier promotes the dispersion of the modified activated carbon on the 3D printing carrier channel, thereby providing more active sites.
[0060] Embodiment 3:
[0061] (1) Preparation of modified activated carbon:
[0062] The activated carbon was vibrated and ball-milled at a frequency of 100 Hz for 15 min to obtain modified activated carbon with an average pore size of 0.16 mm;
[0063] (2) Preparation of 3D printing carrier:
[0064] Pour 2g of photosensitive curing resin into the resin tank of the DLP 3D printer, and load the STL file of the three-dimensional ordered variable porous structure into the slicing software, and print according to the set model parameters (layer thickness 0.05mm, exposure time 2.0s, light off time 0.5s, bottom exposure time 45.0s, Z-axis lifting distance 6.00mm, bottom layer number 6 layers). After printing, clean the uncured resin on the outer surface of the 3D printing carrier with ethanol and pure water, dry to constant weight, and obtain a 3D printing carrier with a three-dimensional ordered variable porous structure. The specific surface area of the obtained 3D printing carrier with a three-dimensional ordered variable porous structure was tested and measured to be 44m 2 g -1 .
[0065] (3) Modified activated carbon loaded on 3D printing carrier:
[0066] The 3D printed carrier with a three-dimensional ordered variable porous structure was placed in a beaker containing modified activated carbon material, the vortex mixer vibration frequency was adjusted to 50 Hz, and the beaker was vibrated steadily to ensure that the modified activated carbon was fully in contact with the carrier. The modified activated carbon was loaded on the carrier through the electrostatic interaction between the modified activated carbon and the resin. After vibrating for 10 minutes, the 3D printed carrier was taken out, and the 3D printed carrier was washed with deionized water to remove the activated carbon that was not firmly attached. The model was dried to finally obtain a composite catalyst with a three-dimensional ordered variable porous structure loaded with modified activated carbon. The loading mass of the modified activated carbon was 1.50±0.05g obtained by weight measurement yx.
[0067] Comparative Example 1:
[0068] The experimental process was the same as that of Example 2, except that no modification was performed on the activated carbon. A composite catalyst loaded with activated carbon was prepared, and the loading mass of the unmodified activated carbon was 0.75±0.05 g as determined by weight yx.
[0069] Comparative Example 2:
[0070] The experimental process is the same as that of Example 2, except that the activated carbon is ground in a mortar to obtain modified activated carbon, and a composite catalyst loaded with modified activated carbon is prepared. The loading mass of the modified activated carbon obtained by weight measurement yx is 0.75±0.05g.
[0071] Comparative Example 3:
[0072] The experimental process is the same as that of Example 2, except that the photosensitive curing resin is poured into the resin tank of the DLP 3D printer, and the STL file of the solid cylindrical structure (obtained at https: / / www.thingiverse.com / ) is loaded into the slicing software, and printed according to the set model parameters (layer thickness 0.05mm, exposure time 2.0s, light off time 0.5s, bottom exposure time 45.0s, Z-axis lifting distance 6.00mm, bottom layer number 6 layers). After printing, the uncured resin on the outer surface of the 3D printed model is cleaned with ethanol and pure water, and dried to constant weight to obtain a 3D printed carrier with a solid cylindrical structure. The carrier model is a solid cylindrical structure, and a composite catalyst loaded with modified activated carbon is prepared. The specific surface area of the obtained solid cylindrical 3D printed carrier was tested, and it was measured to be 5.34cm 2 g -1 The loading mass of the modified activated carbon was 0.75±0.05 g as determined by weight yx.
[0073] The composite catalyst loaded with modified activated carbon prepared in this comparative example was analyzed by scanning electron microscope. Figure 3 Show. Figure 3 The model diagram of the 3D printing carrier prepared for Comparative Example 3. By comparison Figure 2 and Figure 3 It can be seen that the 3D printing carrier with three-dimensional ordered variable porous structure in Example 2 has a diameter of 16 mm and a height of 32 mm, with orderly pore arrangement and complex structure. The 3D printing carrier (1.5 mL) with the same resin consumption of a solid cylindrical structure has a height of 9 mm when the diameter is maintained at 16 mm. The volume and porosity of the two catalysts were measured by the Archimedean method, and the average of the three measurement results was taken. The results are shown in Table 1.
[0074] Table 1 Surface area, volume and porosity of two 3D printed models with different structures
[0075]
[0076] It can be found from Table 1 that the surface area of the 3D printing carrier with three-dimensional ordered variable porous structure in Example 2 is 6362 mm 2 , the porosity is 72%. And the volume is 1800mm 3 When the surface area of the 3D printing carrier with three-dimensional ordered variable porous structure is much larger than that of the 3D printing carrier with solid cylindrical structure, more than seven times.
[0077] Comparative Example 4:
[0078] The experimental process is the same as that of Example 2, except that 2 g of photosensitive curable resin and 0.75 g of modified activated carbon are mixed and stirred uniformly to obtain a premixed solution. The premixed solution is printed according to the set model. The uncured resin on the surface of the finished print is immediately cleaned with ethanol and pure water, and dried to constant weight to obtain a three-dimensional ordered variable porous structure 3D printed monolithic catalyst.
[0079] Embodiment 4:
[0080] The composite catalysts prepared in Examples 1-3 and Comparative Examples 1-4 and the activated carbon before and after modification in Example 2 were used to degrade ofloxacin, as follows:
[0081] Ofloxacin (OFL) degradation experiment was carried out in FBR, and the composite catalyst was pushed until the catalyst was fixed by tablets and glass balls. 1L simulated wastewater (containing 25mg OFL) was introduced into FBR by a peristaltic pump (simulated wastewater flow rate was 0.0125L / h), 4mL of potassium persulfate solution was added according to 0.4g / L, and then the composite catalyst prepared by Examples 1-3 and Comparative Examples 1-4 was added to react. After sampling every 10min, the absorbance was measured by a UV-visible spectrophotometer at a wavelength of 288nm, and the concentration of ofloxacin in the solution during the reaction was determined according to the absorbance. OFL conversion rate was calculated according to the following formula:
[0082]
[0083] Where, C0 is the initial absorbance of OFL conversion, and C1 is the absorbance of OFL at reaction time (t).
[0084] The results are as follows: after 40 minutes of reaction, the ofloxacin removal rate of the composite catalyst in Example 1 is 66.7%, the ofloxacin removal rate in Example 2 is 89.5%, the ofloxacin removal rate in Example 3 is 75.5%, the ofloxacin removal rate in Comparative Example 1 is 46.7%, the ofloxacin removal rate in Comparative Example 2 is 53.4%, the ofloxacin removal rate in Comparative Example 3 is 29.5%, and the ofloxacin removal rate in Comparative Example 4 is 42.3%.
[0085] The catalytic performance of the composite catalysts prepared in the above Examples 1-3 is compared with that in Comparative Example 1. The composite catalyst prepared by unmodified activated carbon in Comparative Example 1 has a degradation effect of 46.7% on ofloxacin, which is lower than that of the composite catalyst prepared by modified activated carbon in Examples 1-3. It can be seen that modification of activated carbon is a key factor affecting the activity of the catalyst.
[0086] The catalytic performance of the composite catalysts prepared in the above examples 1-3 is compared. Figure 4When the vibration ball milling frequency in Example 2 is 40 Hz, the degradation effect of ofloxacin is as high as 89.5%, which is higher than 66.7% in Example 1 and 75.5% in Example 3. It can be seen that the vibration milling frequency is a key factor affecting the catalyst activity.
[0087] The catalytic performance of the composite catalyst prepared in Example 2 and Comparative Example 3 is compared. Figure 5 The degradation effect of ofloxacin in Example 3 is 89.5%, which is 29.5% higher than that of the composite catalyst with a solid cylindrical structure in Comparative Example 3. This shows that the 3D printed carrier structure is a key factor affecting the catalyst activity.
[0088] The catalytic performance of the composite catalyst prepared in the above Example 2 and Comparative Example 4 is compared. In Comparative Example 4, the monolithic catalyst obtained by doping the modified activated carbon in the photosensitive resin has a degradation effect of 42.3% on ofloxacin, which is lower than the composite catalyst obtained by loading the modified activated carbon on the 3D printed carrier structure in Example 2. The possible reason for this phenomenon is that during the catalyst printing process, the modified activated carbon and the photosensitive resin are delaminated, resulting in stability problems of the catalyst.
[0089] Embodiment 5:
[0090] In order to investigate the stability of the composite catalyst prepared in Example 2, a long-term degradation experiment was carried out using the experimental process of Example 4 (the simulated wastewater flow rate was 0.0125 L / h). Figure 6 As shown in the figure, the catalyst has good stability. With the increase of the number of uses, the catalytic activity only slightly decreases. Cycle 1 shows the best performance, with an OFL removal rate of 89.5%. The removal rates of cycles 2, 3, 4 and 5 are 83.7%, 79.9%, 75.4% and 72.9%, respectively. Therefore, the composite catalyst has good recycling performance and a long service life. In addition, the 3D printed composite catalyst shows excellent stability and meets the requirements of potential industrial applications.
Claims
1. A 3D printed structure-supported carbon material composite catalyst, characterized in that: The catalyst is prepared by loading a modified carbon material on a 3D printed carrier, and the modified carbon material is obtained by vibrating and ball milling the carbon material.
2. The 3D printed structure-supported carbon material composite catalyst according to claim 1, characterized in that: The carbon material is one or more of graphene, carbon nanotubes, activated carbon, and biochar, and the material of the 3D printing carrier is one or more of vinyl resin, polyurethane resin, epoxy resin, and photosensitive curing resin.
3. The 3D printed structure-supported carbon material composite catalyst according to claim 1, characterized in that: The structure of the 3D printing carrier is a three-dimensional ordered variable porous structure, a structure containing parallel straight channels, an ordered mesh structure or a honeycomb structure.
4. The 3D printed structure-supported carbon material composite catalyst according to claim 1, characterized in that: The average particle size of the loaded modified carbon material is 0.1-2 mm, and the loaded mass of the modified carbon material is 0.50-5.00 g / 1-50 m 2 g -1 Specific surface area of 3D printing carrier.
5. The 3D printed structure-supported carbon material composite catalyst according to claim 1, characterized in that: The frequency of the vibration ball mill is 10-100 Hz.
6. The method for preparing a 3D printed structure-supported carbon material composite catalyst according to any one of claims 1 to 5, characterized in that: The steps include: (1) Preparation of modified carbon material: treating carbon material by vibration ball milling to obtain modified carbon material; (2) Preparation of 3D printing carrier: pour the 3D printing carrier into the slot of the DLP 3D printer, load the STL file of the required 3D structure into the slicing software, print, clean and dry according to the set model printing parameters to obtain the 3D printing carrier; (3) Loading the modified carbon material on a 3D printed carrier: placing the 3D printed carrier into the modified carbon material, and oscillating the modified carbon material to load the 3D printed carrier, thereby obtaining a 3D printed structure-loaded carbon material composite catalyst.
7. The preparation method according to claim 6, characterized in that: In step (2), the model printing parameters are layer thickness 0.05 mm, exposure time 2.0 s, light off time 0.5 s, bottom exposure time 45.0 s, Z axis lifting distance 6.00 mm, and the number of bottom layers is 6.
8. The preparation method according to claim 6, characterized in that: In step (3), the frequency of oscillation is below 50 Hz.
9. Use of the 3D printed structure-supported carbon material composite catalyst according to any one of claims 1 to 5 in the treatment of organic wastewater by activated hydrogen peroxide and / or persulfate oxidation.
10. The use according to claim 9, characterized in that: The organic wastewater contains antibiotics. The reaction conditions for the 3D printed structure-loaded carbon material composite catalyst used to activate hydrogen peroxide and / or persulfate oxidation to treat the organic wastewater are: normal pressure, the reaction atmosphere is one of air, oxygen, and nitrogen, the reaction temperature is 10 to 80°C, the dosage of hydrogen peroxide and / or potassium persulfate is 1 to 20 times the content of the antibiotic, and the dosage of the 3D printed structure-loaded carbon material composite catalyst used in any one of claims 1 to 5 is 1 to 20 times the content of the antibiotic.